EFL Teacher’s Instructional Design in Conducting Online Learning during the Covid-19 Pandemic - Liza Amelia Syafitri; Yousef Bani Ahmad; Abdul Kodir Al-Baekani (Edumaspul: Jurnal Pendidikan, 2021)
Instructional design is the art of creating and developing trainning experiences that make learning more efficient, effective and enjoyable for students (Merrill, 2012). This study aimed: (1). To find out how do teachers design online instruction during the Covid-19 pandemic; (2). To find out how are teachers perception in conducting online instructional design during the covid-19 pandemic. The participant of this study were an English teacher of senior high school in Karawang. This study used a qualitative narrative design. The instrument used for collecting the data is interview guideline that explained in the form of narrative inquiry. The result showed that by analyzing and understanding students’ characteristic, the teacher could create online instructional design that suitable with the students’ desire in learning. Meanwhile, related to teacher’s perception, in conducting online instructional design in this pandemic. It made the teacher is difficult to carry out the learning materials effectively and achieve the maximum of learning process. In addition, the teacher had to adapt with a new system and it required her to be more creative and innovative in order the student had a motivation in learning during this pandemic. To all of this fact, it can be said that conducting online instructional design made teacher experiencing difficulties while preparing and applying the instruction.